ANALISIS FAKTOR YANG MEMPENGARUHI KEPERCAYAAN DIRI PADA SISWA KELAS IV SDN 14 KELAKIK - Irnawati, Irnawati; Mardiana, Mardiana; Khoiri, Ahmad (JURNAL PENDIDIKAN DAN PEMBELAJARAN SEKOLAH DASAR, 2023)
In essence, humans have a sense of self-confidence, but there is a difference between one and the other, namely some have low self-confidence and some heve high self-confidence. Confidence is needed wherever a person is, therefore self-confidence needs to be bulit and developed positively and objectively. Students as students who function as subjects of education are required to be able to adapt to changes. This study aims to determine the factors that affect self-confidence in grede IV SDN 14 Kelakik. The problem at hand is what are the factors that affact the low self-confidance of grade IV students at SDN 14 Kelakik? Data collection techniques were carried out using observation, interviews and documentation. this study uses a deskriptive method with a qualitative approach. The results of this study indicate that there are manyfactirs that affect students self-confidence, such as peer factorsd, parents, school and physical condition. and it is parents who are very prominent in the peer factor, because students who feel insecure coming to the front of the class are often ridiculed by their classmates, this factor is evident from the results of interviews conduducted the are 3 students out of 13 students. Parental factors, as evidenced by the results of interviews theree were 5 students who lacked confidence because parents where busy and did not understand so they could not accompany children in learning and doing assignment. Based on the results of this reseacerch, it is time for to no longer view schools as the only educational institutions in an effort to instill and grow life values, instead, parents must also play an aktive role fostering a positive attitude.